Calibration of Inductance Using a PXI-Based Maxwell–Wien Bridge from 20 Hz to 20 kHz - Mohamed Ouameur; Emmanuel Patois (Metrology, 2025)
This paper presents a Maxwell–Wien bridge for use in the calibration of standard inductances with values between 100 µH and 10 H and frequencies from 20 Hz to 20 kHz. The inductances are measured by comparison with a variable standard capacitor, in parallel association with a variable standard resistor, on the bridge modified by a Wagner balance. The variable standards are calibrated after the bridge balance. The other resistors in the bridge are standard resistors, pre-calibrated in AC using an automatic Wheatstone bridge and in DC after the bridge has been balanced using a comparison bridge with standard resistors traceable to the quantum Hall effect standards. PXI modules are used to supply the bridge with two voltages controllable in amplitude and phase. Design details and the uncertainty budget are discussed. For an inductance of 100 mH characterized by an internal resistance of 83 Ω, the expanded uncertainties are less than 6 µH on the inductance and 20 mΩ on the internal resistance. For inductances from 100 µH to 10 H, the relative uncertainties are less than 0.02% of the inductance and 0.2% of the internal resistance from 20 Hz to 20 kHz.